Postpartum Care Education for Postpartum Patients at A.M Parikesit Tenggarong Hospital - Tri Wulandari; Tri Wahyuni (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Postpartum or postpartum is one of the risk periods that is a factor causing death in mothers, so it is necessary to carry out strict monitoring and proper postpartum care. WHO reports that as many as 30% of mothers die during postpartum due to problems and complications of postpartum. The purpose of this community service is to provide postpartum care education to postpartum mothers. The method used is to provide material using power points, questions and answers, and sharing experiences. The partners of this activity are 11 postpartum mothers at the A.M Parikesit Tenggarong Hospital. The results of this activity show that there is an increase in postpartum care knowledge after education.